Conocimiento sobre sexualidad en estudiantes del Bachillerato del colegio Beatríz Cueva de Ayora y Unidad Educativa Anexa a la UNL de la ciudad de Loja. Octubre 2013. - Hurtado Alvarado, Lilia Valeria (2013)
The present investigation is a descriptive and transverse study, it was realized by the aims of: to determine the type of information that the teenagers have with regard to the sexuality and the conception, to know the percentage of pregnant women who are present at the establishments, to identify which are the most frequent ages of pregnancy in the teenagers, and finally to establish the level of knowledge on contraceptive methods in students of the Baccalaureate of the Colleges Beatriz Cueva de Ayora and Annexe to Loja's National University. We worked with a population of 302 students randomly selected for 1st, 2nd and 3rd year of high school, whose ages are between 14 and 19 years old, using the survey to obtain information, which were tabulated and processed to draw conclusions and while making recommendations based on the results Among the main results in the educational units investigated was found: that 71% of the study population does not adequately define sexuality, 35% of students agree that the information on sexuality and conception received is good, 35% of students agree that information on sexuality and conception received is good, of 3 % of pregnant teenagers was demonstrated that the age more frequent of pregnancy is 17 years corresponding to 37 %, Likewise 93 % of the students has knowledge adapted on methods contraceptive. KEYWORDS: KNOWLEDGE, ADOLESCENT, SEXUALITY, SEXUAL EDUCATION